EAGLE DANCE AS CULTURAL IDENTITY IN THE ISOLATING TRIBAL COMMUNITY CHANGES, IN PEMATANG KABAU VILLAGE, AIR HITAM DISTRICT, SAROLANGUN REGENCY, JAMBI PROVINCE - Purnama, Sri; Dibia, I Wayan; Suastika, I Made; -, Daryusti (E-Journal of Cultural Studies, 2010)
This dissertation discusses the Eagles dance as the identity of dance incultural change in isolated tribal community (SAD), in the village of PematangKabau, Air HItam District, Sarolangun Regency, Jambi Province. CentralGovernment through the Ministry of Social Affairs moved SAD out of the jungleand then settling on a permanent area and this activity has been carried out since1973. Furthermore, the settlement resulted in a fairly fundamental change, notonly in style and environment of SAD, but more important to the identity markersand self-identity of SAD.People of SAD who had been settled, strive to keep eagle dance even bymaking some changes as far as not to break out the essential elements of the Eagledance in order to avoid a total loss of identity and their self-identity in the newneighborhoods, This study aims to see how art, in this case Eagle dance, can be amarker of identity that attaches to the SAD after they settle outside the forest. Toachieve these objectives there are three main problems which will be soughtanswers in this study, namely: (1) What does the Eagles dance of SAD in thevillage of Pematang Kabau looks like?; (2) how is the status of the Eagles dancefor SAD in the village of Pematang Kabau; and (3) how is the impact andmeaning of Eagles dance towards the SAD changes?The study with the perspective of cultural studies designing as thisqualitative research is used to solve the three problems mentioned above by usingseveral concepts, theories and techniques of data collection. Concepts are referredto Eagle dance, cultural identity, change, and isolated tribal community. Thetheory used is the identity theory, the theory of semiotics, hegemony theory, andtheory of deconstruction. Data collection techniques include participantobservation, depth interviews, and study of literature / documentation. The datacollected is processed in a descriptive analytical and subsequently presented in theform of narrative, tables, and visual illustrations.The results indicate that there had been changes towards the Eagles dancein SAD which had settled in Kabau Pematang village, although the use of holy spells as a musical accompaniment and distinctive gestures symbolic of this danceis still maintained. In residential SAD, Eagle dance is treated as a cultural groupidentity, and the regeneration of the dancers began to be conducted. The impact ofthis treatment which is carried out by citizens of SAD making the Eagles dancebecomes sustainable dance despite the new of its socio-cultural functions. ForSAD in residential areas, Eagle dance means as a symbol of cultural expression,equality, and welfare. The main meaning of Eagles dance, who built fromtradition and cultural power of SAD, becomes a representation of communitygroups concerned, in the midst of pressure, domination and influence of themajority culture.